The Level of Achievement Goals Orientation to Basic Sixth Grade Pupils and its Relationship with Gender and Kind of School - مبيض, مهند; القاضي, لمى; شيحا, سماح (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aimed at assist the level of Achievement Goals Orientation to basic sixth grade pupils and to identifying the relationship with gender and kind of school. For that, the descriptive method was used, and prepared a reliable validate scale to measure Achievement Goals Orientation. The simple random sample consisted of (150) pupils in Lattakia city schools. The results showed that pupils the level of Achievement Goals Orientation and in each in each goal (Mastery-Approach, Performance-Approach) was high, and was moderate in each goal (Mastery-Avoidance, Performance-Avoidance). In addition, There were significant differences among Females and male` scores on scale of Achievement Goals Orientation in general and in each goal (Performance-Approach, Performance-Avoidance, Mastery-Avoidance) in favor of male, and There were no significant differences among Females and male` scores on Mastery-Avoidance. There were no significant differences due to the kind of school in general and in each goal too. So, the research recommended in the light of the results of study to Necessity of the use of Mastery-Approach and Performance-Approach among pupils for development of learning outcomes.